Illinois Community Colleges Expanding Opportunities. A Guide to Quality, Affordable, Educational Opportunities...Very Close to Home. - Illinois Community Coll. Board, Springfield; Illinois Community Coll. Board, Springfield ([Washington, D.C.] : Distributed by ERIC Clearinghouse, 1990)
Designed as a recruitment pamphlet and general information guide for prospective students, this booklet contains two comprehensive charts on the 240 programs offered, and the degrees and certificates available at each of the 49 campuses in the Illinois Community College system. The first chart indicates which campuses in the system offer Associate in Arts, Associate in Science, and General Associate degrees and/or certificates. The second chart provides information on degrees and certificates available for each program at each campus. Individual programs are listed under the following broad areas of study: (1) Agriculture & Natural Resources, comprised of 6 separate programs including conservation and horticulture; (2) Business Occupations, comprised of 24 programs including accounting, food marketing, and real estate; (3) Communications, comprised of 8 programs including advertising and journalism; (4) Construction Trades, comprised of 6 different programs; (5) Food Production and Management, consisting of 6 programs including baking and meat cutting; (6) Health, comprised of 26 programs including dental services and respiratory therapy; (7) Mechanics & Repairers, consisting of 10 programs including auto body repair and watch and clock repair; (8) Public, Personal & Social Services, consisting of 19 separate programs; (9) Technologies, comprised of 32 different programs including drafting, plastics, and robotics; and (10) Transportation, comprised of airplane pilot, aviation management, and truck driving programs. The pamphlet includes a directory of all public community colleges in Illinois, and a map of the state showing the location of each of the colleges. (GFW)
May also be available online. Address as at 14/8/18
Microfiche.
Keywords: Allied Health Occupations Education; Associate Degrees; Business Education; College Programs; Community Colleges; Educational Certificates; Program Guides; Student Recruitment; Technical Education; Two Year Colleges; Vocational Education; Illinois; Reports, Descriptive